Utøya rører dig i hjertet - om hvidhed, nationalisme og nordiskhed - Nielsen, Asta Smedegaard (Kvinder, Køn & Forskning, 2015)
From analyses of newscasts and interviews with journalists, the article studies how affective orientations in relation to the 22 July terror and its victims entail constant displacements of the represented ’us’. Through the affective work of mourning, compassion and disbelief it moves between representations of whiteness, Nordicness, Danishness/Norwegianness, and humanity in general. This involves strategies to ward off that a common white Nordicness, embodied by Breivik, can work to make ’us’ alike him. By separating ’the Danish’ from ’the Norwegian’ the terror is upheld as a purely Norwegian problem. And by the inclusion of non-white bodies, whiteness is erased as something that could represent ’us’. I suggest that this work is partly driven by the reinstatement of proper masculinities as the nation’s representatives obstructing Breivik’s claim to act in defence of the nation. In spite of this critical reading the article does spot some openings that mourning and compassion can work in an inclusionary way, in terms of giving way to a common humanity being demarcated by the evil of a traumatic act, as the 22 July terror.